Synthesis and Diagnosis of Nucleoside Analogues and Cytotoxic Effects against Normal Human Lymphocytes - Najeeb Ibraheem Mohamed (Journal of Global Pharma Technology, 2018)
Synthesis of nucleoside analogues and investigated that cytotoxic effects on the Normal Human Lymphocyte by MTT assay. Preparation of Mannich bases that derivative from thymidine fainally obtain crystals and purify by using silica gel filled with gasoline. In the current study is to evaluate the cytotoxic effects for the four compounds of nucleoside analogues at concentrations of (0.15mg/ml, 0.31mg/ml, 0.62mg/ml, 1.25mg/ml, 2.5mg/ml, 5mg/ml, 10mg/ml, and 20mg/ml) alongside against the freshly isolated and cultured normal human lymphocyte in vitro. The result refer to that cytotoxic effects of each type of nucleoside analogues used in the study and the growth inhibition rate (%) was associated to the concentration of nucleoside analogues, so that a 20mg/ml concentration of gave the highest growth inhibition rate, followed by the 10mg/ml, 5mg/ml and 2.5mg/ml, 1.25mg/ml concentrations, therefore the cytotoxic effects was concentration dependent. There was a significant difference between the concentrations when compared between the four kinds of nucleoside analogues, also statistical analysis related between the effects of different kind of nucleoside analogues showed great difference and there was a significant relationship between the inhibition rate and the concentrations of the materials tested (P ˂ 0.05). The results visibly showed that nucleoside analogues have strong cytotoxic and cytostatic effects on studied the lymphocyte and the cytotoxic effects may be attributed to the role of these compounds in the DNA and RNA synthesis or play a role in the apoptosis. On the basis of these results we can conclude nucleoside analogues have potent cytotoxic effects against human lymphocytes in vito and the pathways for how the cells dies need further studies in the future studies in more details and more advanced tests and techniques.Keywords: Nucleoside analogues; Cytotoxicity; Normal human lymphocyte.